Implementasi Aplikasi Keuangan 69 Volley Ball Club Berbasis Web - Yunianto Purnomo; Ary Budi Warsito; Eliando; Athasya Nanda Haryani (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
69 Volley Ball Club is one of the volleyball associations located in Tangerang Regency, Banten, whose performance is getting better in terms of achievements and the number of athletes. To improve the services of athletes, coaches, training administration, matches, and financial administration, it is necessary to create a computer application that can help record data automatically. The cash flow information system for 69 Volley Ball Club is designed to be web-based so that it can be easily accessed anywhere. The development methodology used to build this cash flow information system is by using the object oriented method: Unified Modeling Language (UML). The system design is described using Activity Diagrams, Use Case Diagrams, Use Case Descriptions, Sequence Diagrams and Mockup views. The results of the design, a cash flow application program was made by the Laravel framework. The implementation stage begins with a field study using the observation method, by observing directly the administrative activities at the 69 Volley Ball Club in order to obtain explanations and obtain data that will be needed in designing of the information systems. Then the design was made which was finally implemented in the form of a web-based 69 Volley Ball Club financial application program.